KAJIAN MODEL INTERNALISASI IDEOLOGI KEBANGSAAN DI DAERAH PERBATASAN - Mas'ud Said (JURNAL KEBIJAKAN PUBLIK, 2018)
Research on Indonesia’s national ideology as a glue of national identity, has been one of the most interesting theme in the study of modern Indonesia. Due to its geographical condition, maintaining natinalism of the people living in the border area is one of the changes of Indonesian government. The mode of internalization of  national ideology is needed. This research describes about the common problems faced by people living in the  borders areas and the need of searching and development of a mode of internalization of Indonesia’s national ideology. This research found that in general, the people’s feelings to be Indonesian are well mainatined and surprisingly fertilyzed naturally. However, new form of internalization of natinal ideology needed to be organized and applied in the border area to prevent centiments and eradication of national identity. This study examines the existing condition in the three borders areas: (1) NTT – Timor Timur, (2) Papua – PNG and (3). Kalimantan Barat, Kab. Sanggau  – Malaysia. To gather data and information, visit to the border of Sanggau – Entikong was taken place in November  2009. Intensive visit, Interviews, focus group discussion, questionaires are employed in this study.